Students’ Perception on the Use of Mother Tongue by the English Teacher in the Classroom - Destarani, Tiwi; Nurkhamidah, Neni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Language is an important component in learning activities since it plays crucial role to build the communication between teacher and students. One language that is frequently used was mother tongue, especially in English classrooms. Due to this phenomenon, several studies about the use of mother tongue in English classroom and students’ perception about it have been done, however studies that focus on perception by the junior high school students’ especially class VII have not been conducted yet. Therefore, the researcher conducted a study to describe the use of mother tongue by the English teacher in the classroom and to investigate students’ perceptions towards it. The research was conducted at SMPN 189 Jakarta, with 36 students of grade VII D and their English teachers as participants in the study. Observation and Questionnaire are used as qualitative methods to collect data. The results of the study show that English teachers use the mother tongue quite often during learning activities. The use of Mother Language is carried out on every interaction between teachers and students, including questions and answers, commands, and feedback. In addition, the results of the study also show that students prefer to use their mother tongue during English language class.